Influence of face to core layer ratios on technological properties of oriented Strand Board (OSB) of Eucalyptus benthamii Influência do arranjo das camadas do colchão nas propriedades tecnológicas de painéis de partículas orientadas (OSB) de Eucalyptus benthamii - Martarello L.P.* (2015)
The objective of the study was to determine the influence of four different arrangements of face to core layer ratios on the technological properties of oriented strand board (OSB) of Eucalyptus benthamii. The particles were obtained from logs of a 13 years old plantation located in Palmeira, Santa Catarina. The experiment consisted of 4 treatments as follows: 100% of particles oriented in the same direction (T1), and crossed layers of 20-60-20% (T2), 25-50-25% (T3) and 30-40-30% (T4). Panels were produced with a density of 0,650 g/cm3, 6% phenol formaldehyde resin, 1% wax sizing and a pressing cycle of 180°C, 40 kgf/cm2 for 8 minutes. The tests were done according to the parameters of ASTM D1037(1993) and DIN 52362(1982) and the results were analyzed by Analysis of Variance and Tukey's Test at 95% probability, as well as by comparison with the parameters of CSA 0437 (1993). The results demonstrated that the panels of medium density values presented below the compression ratio found in the literature and simultaneously high values of water absorption and thickness swelling that did not meet the criteria of the reference standard. For the modulus of elasticity and modulus of rupture, values of stiffness and strength have been enhanced by including a cross-layer in the central part of the panel. Even for modulus of rupture there was no statistical difference among treatments. For internal bonding, all treatments were satisfactory with an average strength of 0.506 MPa strength. According to CSA 0437.0 (1993) for mechanical properties, all treatments were classified as Class 01.